Public policy in an uncertain world : analysis and decisions - Manski, Charles F. (Harvard University Press, 2013)
"Manski argues that public policy is based on untrustworthy analysis. Failing to account for uncertainty in an uncertain world, policy analysis routinely misleads policy makers with expressions of certitude. Manski critiques the status quo and offers an innovation to improve both how policy research is conducted and how it is used by policy makers"--Publisher's description.